EFFECT OF MINERALOCORTICOID RECEPTOR ANTAGONISTS ON CARDIOVASCULAR MORTALITY IN ADULTS WITH HEART FAILURE: AMETA-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - DAS, PRANAB; PAL, MAHAPRASAD; AKRAM, WASIM; DAS, BODHISATYA (International Journal of Current Pharmaceutical Research, 2026)
Objective: To evaluate the effect of mineralocorticoid receptor antagonists on cardiovascular mortality in adults with heart failure using evidence from randomized controlled trials. Methods: A systematic review and meta-analysis of randomized controlled trials was conducted in accordance with PRISMA 2020 guidelines. Electronic databases, including PubMed, Scopus, Google Scholar, and the Cochrane Central Register of Controlled Trials were searched for eligible studies. Trials enrolling adult patients with heart failure and comparing MRAs with placebo were included. Cardiovascular mortality was the primary outcome. Risk ratios (RRs) with 95% confidence intervals (CIs) were calculated for individual studies and pooled using an inverse-variance fixed-effect model. Statistical heterogeneity was evaluated using Cochran’s Q test and the I² statistic. Risk of bias was assessed using the Cochrane Risk of Bias tool, and certainty of evidence was evaluated using the GRADE framework. Results: Three large, double-blind randomized controlled trials comprising 11,032 patients met the inclusion criteria. Treatment with MRAs was associated with a significant reduction in cardiovascular mortality compared with placebo. The pooled analysis demonstrated a 20% relative reduction in cardiovascular mortality (pooled RR = 0.80; 95% CI: 0.73–0.86). No significant heterogeneity was observed among the included studies (I² = 0%). All trials were judged to have a low risk of bias, and the certainty of evidence for the primary outcome was rated as high. Conclusion: Mineralocorticoid receptor antagonists significantly reduce cardiovascular mortality in patients with heart failure. These findings provide high-certainty evidence supporting their use as an essential component of guideline-directed medical therapy.